2021
DOI: 10.34172/apb.2022.031
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Stability of Two Anti-Hyperpigmentation Agents: Kojic Acid as a Natural Metabolite and Its Di-Palmitate Ester, Under Oxidative Stress; Application to Pharmaceutical Formulation Design

Abstract: Purpose: Kojic acid a natural metabolite (KA) and its dipalmitate ester, kojic acid dipalmitate (Kadp) are both prescribed to treat skin hyperpigmentation. Stress test reveals the intrinsic stability of active ingredients and leads to selection of the suitable formulations. This research evaluates the comparative stability of KA and its di-palmitate ester under liquid oxidative stress. Methods: The HPLC-UV/PDA method with a C18 column was utilized. Liquid oxidative stress was induced using hydrogen peroxide (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Of note, a decrease in KDP content does not necessarily mean loss of activity, given that KDP can be hydrolyzed to kojic acid. Another possibility for the degradation of KDP and its loss of content is the oxidation of the molecule, which can occur in liquid oxidative stress conditions, as mentioned by Tazesh et al (2021) [ 21 ], leading KDP to suffer oxidative degradation, with the suggested mechanism being ring opening [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, a decrease in KDP content does not necessarily mean loss of activity, given that KDP can be hydrolyzed to kojic acid. Another possibility for the degradation of KDP and its loss of content is the oxidation of the molecule, which can occur in liquid oxidative stress conditions, as mentioned by Tazesh et al (2021) [ 21 ], leading KDP to suffer oxidative degradation, with the suggested mechanism being ring opening [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…KDP content was determined using a high-performance liquid chromatograph coupled to an ultraviolet detector (HPLC–UV) at 250 nm [ 21 ]. Samples were dissolved in THF, acetonitrile, methanol, purified water, and acetic acid (35:30:29:5:1) and kept in an ultrasonic bath for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC is a versatile technique to evaluate the drug concentration after in transdermal preparations. [21][22][23] A previously validated HPLC method was used for quantitation analyses. 12 To revalidate the method, specificity and linearity parameters were calculated in the same condition as analyzed samples.…”
Section: Resultsmentioning
confidence: 99%
“…The stress tests reveal the intrinsic stability of the active ingredients and can be useful in developing a suitable formulation with satisfactory quality and shelf life [ 55 ]. Several accelerated stability tests have been suggested for the prediction of long-term stability, such as storage at elevated temperatures [ 56 ], under an accelerated or different type of light exposure [ 57 , 58 ], and under oxidative stress [ 55 , 59 ]. Honokiol is known to act as an antioxidant because of high radical-scavenging activities determined by the presence of two hydroxyl groups at the ortho - and para -positions [ 60 ].…”
Section: Discussionmentioning
confidence: 99%